IN VITRO STUDIES ON THE ANTI-INFLAMMATORY EFFECTS OF ESSENTIAL OIL OF Rosmarinus officinalis L. IN MACROPHAGE CELLS (Applied Biological Research, 2024)
The use of plant-based drugs against various human disorders have attained global interest. Multicomponent essential oils are used to cure inflammation- related disorders. The present study was aimed to assess the anti- inflammatory potential of essential oil from Rosmarinus officinalis (EO- RO) using in vitro model of LPS-activated RAW macrophage cell lines.EO-RO was hydro-distilled using Clevenger apparatus and evaluated first for protein denaturation and proteinase inhibitory activities, followed byassays for cyclooxygenase (COX) and lipoxygenase (LOX) activities in RAW 264.7 macrophage cell lines. The data was statistically analysed by one-wayanalysis of variance. Dose-dependent inhibition was observed in protein denaturation with 50 μg mL-1 EO-RO exhibiting a maximum inhibition of 67.77%. Similarly, proteinase inhibitory assay depicted 72.47% inhibition.The COX and LOX activities showed increased inhibitions in dose-dependent manner i.e. 25 to 100 μg mL-1 EO-RO displayed 58.72 and 75.33%; 28.58- 40.86% inhibition, respectively.
Keywords: Anti-inflammation; essential oil; macrophage cells; protein denaturation; Rosmarinus officinalis